1991
DOI: 10.1096/fasebj.5.8.1850705
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metalloproteinases and their inhibitors in connective tissue remodeling

Abstract: Matrix metalloproteinases are an important group of zinc enzymes responsible for degradation of the extracellular matrix components such as collagen and proteoglycans in normal embryogenesis and remodeling and in many disease processes such as arthritis, cancer, periodontitis, and osteoporosis. A matrixin family is defined, comprising at least seven members that range in size from Mr 28,000 to 92,000 and are related in gene sequence to collagenase. All family members are secreted as zymogens that lose peptides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

34
2,044
7
73

Year Published

1995
1995
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 3,121 publications
(2,167 citation statements)
references
References 60 publications
34
2,044
7
73
Order By: Relevance
“…MMPs 1 and 13 were selected as they are known to be active against fibrillar collagens, including the predominant collagen type I 1, 28, 29, 30. MMP‐3 was selected as it degrades other minor proteins in tendon matrix, including collagens III, IV, IX, and X, and also proteoglycans and elastin 28, 29, 30, 31, 32, 33. The C1,2C (or COL 2 3/4C short) antibody detects the carboxy terminus of fragmented type I and II collagen, cleaved by collagenases MMP‐1, MMP‐8 or MMP‐13 21, 34, 35, 36, 37…”
Section: Methodsmentioning
confidence: 99%
“…MMPs 1 and 13 were selected as they are known to be active against fibrillar collagens, including the predominant collagen type I 1, 28, 29, 30. MMP‐3 was selected as it degrades other minor proteins in tendon matrix, including collagens III, IV, IX, and X, and also proteoglycans and elastin 28, 29, 30, 31, 32, 33. The C1,2C (or COL 2 3/4C short) antibody detects the carboxy terminus of fragmented type I and II collagen, cleaved by collagenases MMP‐1, MMP‐8 or MMP‐13 21, 34, 35, 36, 37…”
Section: Methodsmentioning
confidence: 99%
“…Enzymes of this family, such as tissue collagenase (MMP-1), stromelysin-1 (MMP-3), type IV collagenase (or gelatinase A, MMP-2) and gelatinase B (MMP-9) are secreted as zymogens, and once activated, they are able to remove connective tissue during normal turnover and pathologic breakdown [5]. The latent form (proenzyme) can be activated, at least "in vitro", by other proteases (e.g., plasmin, plasma kallikrein, tissue plasminogen activator, which are present in the inflammatory micro-environment), as well as by mercurials (e.g., 4-aminophenylmercuric acetate) [6].…”
Section: Introductionmentioning
confidence: 99%
“…To date, it seems that tissue remodeling in both normal and pathological states is dependent on matrix metalloproteinase (MMP) activities. On the other hand, some MMPs such as the 92 and 72 kDa collagenases were found to be structurally related to fibronectin [10,15]. In the present work, we have shown that after limited digestion of an intact basement membrane, collagenase/gelatinase activities are expressed.…”
Section: Resultsmentioning
confidence: 47%